Peran Orang Tua Sebagai Agen Sosialisasi Dalam Membentuk Kepribadiaan Anak - Farista, Zeni (Paradigma, 2021)
Abstract Socialization and Formation of Personality is very important for everyone in social life. Because by socializing we can get to know each other. Socialization can be interpreted as a process of planting or transferring habits or values ??and rules from one generation to another in a group or society. In socializing, parents have a very important role. Because, the first socialization agent in shaping a child's personality is the parents. Therefore, parents must socialize as well as possible to children so that the child's personality is also good. Some of the benefits that we get from socialization are that a person is able to become a good member of society, a person can adjust his behavior according to society's expectations, a person will know himself better in his social environment and a person will be aware of his existence in the community around him. This research is using observation techniques, interviews with several parents in Surabaya and literature study. This study uses a qualitative descriptive approach, namely qualitative research that produces descriptive data in the form of both spoken and written words from the observed subjects. This study aims to determine the role of parents as agents of socialization in the formation of children's personalities. The results of this study explain that parents, whose notes are agents of socialization in the family, have an important role in forming positive character or personality for children. It is hoped that later the child will be able and able to become an individual who has a normative personality, has guidelines in carrying out an action. so that later they can become individuals with character and be able to act in accordance with the norms that apply in society. Keywords: socialization, personality, children, family, the role of parents.